Teachers’ Views of the Potential of Art Therapy in Young Learners - Marijanović, Ivana; Kuščević, Dubravka; Reić-Ercegovac, Ina (Revija za elementarno izobraževanje, 2017)
The aim of the study conducted on 205 class teachers was to explore the extent to which they care about their pupil's artistic expression, how much they know about art therapy and it’s potential for young learners, especially when working with abused children and children with developmental disabilities, and their willingness to seek additional knowledge about art therapy. The research results showed no significant difference in art therapy knowledge and its implementation when working with young children according to teachers’ age, work experience or education. Still, the assessment of their own knowledge about art therapy and its potential did differ according to age and level of education.
Keywords: art therapy; class teacher; elementary teacher education; art education; fine arts